The Mediating Role of Meta-Relational Threat Sensitivity on the Relationship between Parental Motivation and Moral Judgments - Beyza Tepe; Sena Cüre Acer (Psikoloji Çalışmaları)
Research shows that parental motivation is associated with moral sensitivity. Previous research also concurs that high levels of parental motivation are associated with high levels of moral sensitivity. This is grounded in the fact that individuals’ needs allow them to bring a child in a society where moral values are preserved and maintained. By extending previous research, the current study aims to examine the mediative role of meta-relational threat sensitivity introduced by Tepe and Aydinli-Karakulak (2019) (evaluating immoral behaviors at the society level) as an individual predisposition on this link. More specifically, individuals’ high levels of parental motivation will be associated with moral wrongness judgments about a violation of social relationships between in-group members such as family or friends (unity violation, e.g., a mother who does not care about her child or an incest relationship between two siblings), through their high levels of community-based meta-relational threat sensitivity. Data (N = 127) were collected from university undergraduates in Turkey. Results showed that there are indirect effects of community-based meta-relational threat sensitivity on the link between parental motivation and moral wrongness judgments of unity violation despite their marginal significance. In addition to contributing meta-relational threat sensitivity as a measure of individual predisposition to the field of moral psychology, the current study not only suggests a mediative role of meta-relational threat sensitivity on the link between parental motivation and moral wrongness judgments but also emphasizes the role of parental motivation (even among nonparents) on the maintenance of the moral systems at the society level. This highlighted further a different perspective on the link between parenting and morality. In simpler terms, high levels of parental motivation are associated with high levels of community-based meta-relational threat sensitivity, which in turn leads to harsher moral wrongness judgments. Moreover, the current study focuses on relationship regulation theory, relational motivations, social conservatism, and life-history strategy to discuss the findings.